Enhancing organizational sustainable innovation performance through organizational readiness for big data analytics. - Arshad, Muhammad; Qadir, Aneela; Ahmad, Waqar; Rafique, Muhammad (Humanities & Social Sciences Communications, 2024)
Organizations must employ big data analytics to maintain sustained innovation in the highly dynamic and evolving business landscape. Even though BDA has a transformative power to revolutionize how businesses do things and engage with their customers' adopting BDA has faced significant challenges, especially in developing countries. This research aims to create a theoretical framework to understand how organizational readiness for BDA can influence sustainable innovation performance. Sampling errors were mitigated through a time-lagged study design, and the data was collected in three phases. The test results using Partial Least Squares Structural Equation Modeling show that organizational readiness is a critical mediator, establishing a robust chain between BDA skills and sustainable innovation performance. The results of this study imply the need for organizational foundation and alignment, which are critical to the compelling strategic deployment of BDA for sustainability innovation performance. Thus, this study can offer a valuable contribution to this topic in the future and a profound implication of the phenomenon at receptive stages.